Derivation of Stem Cell-like Cells From Spherical Culture of Astrocytes for Enhanced Neural Repair After Middle Cerebral Artery Occlusion - Zhu, Dan; Cao, Zheming; Pang, Xiaoyang; Jiang, Wei; Li, Chihao; Zhang, Xing; Tian, Xibin; Tu, Haijun; Wu, Panfeng; Nie, Hemin (Frontiers in Bioengineering and Biotechnology, 2022)
Neural precursor cells (NPCs) tend to aggregate and develop into three-dimensional (3D) spheres, which in return help maintain the stemness of the cells. This close relationship between spherical environment and cell stemness direct us to assume that 3D spheres of astrocytes (ASTs) may facilitate the acquiring of stem cell-like features and generate sufficient seed cells for regeneration of neurons. In vitro results confirmed that mouse ASTs cultured on agarose surfaces spontaneously formed cell spheres and exhibited molecular features similar to stem cells, capable of further differentiating into neurons particularly and forming functional synaptic networks with synchronous burst activities. RNA-sequencing results revealed the similarity of AST-derived stem cells (A-iSCs) to NPCs in global gene expression profiles. The potency of A-iSCs in repairing neural injuries was evaluated in mouse models of middle cerebral artery occlusion (MCAO). It was observed that the transplanted A-iSCs expressed a series of markers for neural differentiation, such as NeuN, Tuj1, and Map2, indicating the conversion of the transplanted A-iSCs into neurons in the scenario. We also found that the injured mice injected with A-iSCs exhibited significant improvements in sensorimotor functions over 8 weeks compared with the sham and control mice. Taken together, mouse ASTs form cell spheres on agarose surfaces and acquire stem cell-associated features, and the derived A-iSCs possess the capacity to differentiate into neurons and facilitate the regeneration of damaged nerves.